Evaluation of PEGylated poly(dimethylaminoethyl methacrylate) based cationic polymers as the gene carrier : The role of molecular weight and molecular architecture - Ong, Wei Lin. (2009)
In order to investigate how variations in molecular weight as well as the structure affects the cytotoxicity and transfection efficiency, copolymers of PEGMEMA and PDMAEMA have been synthesized through reversible addition fragmentation transfer polymerization (RAFT). Through evaluating the biophysical properties of the DNA/polymer complexes, we were able to determine that PEGylation of PDMAEMA can condense DNA into smaller particles, particularly so in low pH and higher N/P ratios. Efficient condensation of DNA can also be achieved at higher pH, with modification in the PEG structure. The relationships of biophysical properties with cytotoxicity as well as transfection efficiency were also examined. Results have shown that with higher molecular weight, the polymers were able to achieve greater transfection efficiency but at a lower cell viability. Different structures of PEG have also played a significant part in the cytotoxicity and transfection capabilities of the polymers. The statistical copolymer showed better cell viability than the brush block and diblock copolymers whereas for transfection efficiency, the statistical copolymer and diblock copolymer showed higher capabilities, depending on the cell line.